Bisociative Knowledge Discovery An Introduction to Concept, Algorithms, Tools, and Applications - Berthold, Michael R. (Lecture Notes in Artificial Intelligence,, 2012)
Modern knowledge discovery methods enable users to discover complex patterns of various types in large information repositories. However, the underlying assumption has always been that the data to which the methods are applied originates from one domain.   The focus of this book, and the BISON project from which the contributions originate, is a network-based integration of various types of data repositories and the development of new ways to analyse and explore the resulting gigantic information networks. Instead of seeking well-defined global or local patterns, the aim was to find domain-bridging associations. These are particularly interesting if they are sparse and have not been encountered before.   The 32 contributions presented in this state-of-the-art survey, together with a detailed introduction to the book, are organized in topical sections on bisociation; representation and network creation; network analysis; exploration; and applications and evaluation.  .